Comparison of metabolic effects of glimepride and sitagliptin with metformin in patients suffering from type 2 diabetes mellitus in a tertiary care hospital - Singh, Preeti; Choudhary, Ruchi; Singh, V. K.; Matreja, Prithpal S. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Diabetes mellitus (DM) is one of the major causes of mortality & morbidity, and patient’s with better control of glycaemic parameters have lesser chronic complications associated with it. Though monotherapy with metformin is first choice for T2DM but is effective in less than 50% of patient and they should be managed with two drug therapy. Both Glimepiride and Sitagliptin are effective with metformin but there has been no study done in this region hence, we planned to study comparison of effects of glimepiride and sitagliptin with metformin in patient of T2DM. Methods: This prospective, open-label, randomized study was done in all patient diagnosed with T2DM, not adequately managed by metformin alone. The patient was divided into two group G (Glimepiride with Metformin) and Group S (Sitagliptin with Metformin) and had a follow up at 3 and 6 months. The biochemical parameters were assessed at 12 weeks and 24 weeks. Results: The result of this study show that both glimepiride and sitagliptin with metformin significantly (p<0.05) lowered both the fasting blood sugar as well as postprandial blood glucose at 3 and 6 months. Glimepiride was more effective in lowering (p<0.05) the plasma glucose at 3 months but both the drugs had comparable result at 6 months. This study also showed that glycosylated haemoglobin was lowered in both groups at three and six months as compared to Day 0 (p<0.05), with glimepiride having better control of glycosylated haemoglobin at 3 months with both groups having comparable result at 6 months. Conclusions: To conclude, this study compared effects of sitagliptin and glimepiride on glycaemic parameters in patients of T2DM and found that both drugs had comparable results.